INDIA’S MARITIME INTERESTS – A ROLE OF COAST GUARD – A PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
India‘s maritime domain is very vast. It stretches from the Persian Gulf to the Malacca Straits, and to the down south in the Indian Ocean. The maritime domain of India is defined by its diverse interests, which stretch out in the respective maritime region with its various maritime installations, economic area of interest and the security and protection of the major assets around the maritime borders. India‘s influence in the Indian Ocean can be seen with its rich glorious maritime history. It‘s active exploration and command over the ocean has enabled numerous empires and traders to benefit immensely from the Indian Ocean. India‘s topography and its geopolitical position in the Indian Ocean unleash both its strength and weakness. Out of the 28 Union States of India, 9 Union States (West Bengal, Odisha, Andhra Pradesh, Tamil Nadu, Kerala, Karnataka, Goa, Maharashtra and Gujarat), 2 Union Territories (Puducherry, Daman and Diu) and in addition are, the two island groups: Lakshadweep and Minicoy in Arabian Sea, and the Andaman and Nicobar in the Bay of Bengal, share maritime boundary, which add to 2.172 million sqkm Exclusive Economic Zone.